Investigating sensorimotor representations, processing and inhibition in Tourette Syndrome: Insights from fMRI, MRS and TMS - Smith, Caitlin Mairi (2025)
Tourette Syndrome (TS) is a hyperkinetic neurodevelopmental movement disorder, characterised by motor and phonic tics, and has been associated with disruptions to cortical inhibition. y-aminobutyric acid (GABA) is the most abundant inhibitory neurotransmitter in the cortex. GABA has been linked to both the integrity of cortical representations and performance in the discrimination of tactile stimuli. In populations with disruptions to cortical inhibitory functioning, such as Focal Hand Dystonia (FHD) which involves involuntary repetitive movements of the hand, abnormalities are evidenced in cortical sensorimotor representations of the fingers and hand muscles. Additionally, individuals with FHD display abnormalities in the processing of sensory stimuli. Many individuals with TS also report experiences of abnormalities in sensory processing, such as premonitory urges (PU) prior to tics and hypersensitivity to external stimuli such as light, sound and touch. However, sensitivity to external stimuli has not been widely investigated in TS, despite being a source of discomfort. Moreover, there is mixed evidence regarding inhibitory abnormalities within the sensorimotor cortices, and a lack of insight into cortical representations of movements relating to tics.